Avaliação da propaganda farmacêutica e do relacionamento do propagandista junto à classe médica - Nascimento, Carlos Alicio (2008)
This work starts from the general objective of measuring the importance of the propagandist in the spreading about the pharmaceutical products to the medical group with the purpose of improving the marketing of relationship used by the representative. The hypotheses that make reference to the possibility of reaching the objectives are based on the variables identified on the daily routine of the representative along with the doctors. To reach a satisfactory conclusion, it was chosen a group of people where it was applied a questionnaire and carried out the analysis of the data. The result proves the necessity of a more aggressive and innovating market policy completely directed to the client with strong investments on the image of the propagandist.